Post-Devolution Household Healthcare Expenditures in Rural Kenya - Omae, Peter Kabuka (European Scientific Journal, ESJ, 2025)
Introduction: Despite improvements in a country’s income during the era of decentralization, catastrophic expenditures persist. This study aimed to establish the determinants of household healthcare expenditures in rural Kenya. Methods: The study utilized data from the Kenya Household Health Expenditure and Utilization Survey (2018). A multiple regression model was employed to estimate the impact of respective determinants on post-devolution health expenditures in rural Kenya. The Ordinary Least Squares (OLS) estimation technique was adopted. Results: The gender of respondents, marital status, medical insurance, and chronic illness were found to be positively related to health expenditures, whereas education levels (primary, secondary, and higher levels) and wealth index (second and third wealth quintiles) were significant predictors but had a negative relationship with health expenditures. Recommendations: The study suggests promoting gender equality in healthcare access and implementing incentives and training programs to encourage men to practice preventive care, thereby reducing hospital visits. Additionally, the study recommends the creation and implementation of awareness programs across organizations, schools, and government agencies. Empowerment programs should be established to help the population lower hospital visits, consequently reducing healthcare expenditures. Furthermore, the government should increase the number of public health facilities to enhance access to subsidized services in rural areas.